REPEAT ENDODONTIC TREATMENT (RETREATMENT): PROBLEMS AND SOLUTIONS - Olimov R.O.,; Axmedova M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: Repeat endodontic treatment, or retreatment, is a necessary intervention in cases of unsuccessful primary root canal therapy, aimed at preserving the tooth and preventing the further progression of infectious and inflammatory processes. Common reasons for the need for retreatment include incomplete canal preparation, inadequate sealing, complications such as cracks or perforations, as well as complex tooth anatomy.